Sustainable Management of Trekking Trails for the Adventure Tourism in Mountains: A Study of Nepal’s Great Himalaya Trails - Upadhayaya, Pranil Kumar (Journal of Tourism & Adventure, 2018)
The existing body of knowledge in tourism reveals that the trekking trails have global appeal and vast potentials to be established and developed as adventure tourism products cum destinations in world mountain regions. The adventure tourism is as one of the fastest growing sub-sectors of tourism. Today the world’s trail systems play a significant role in adventure tourism for its rapid growth. Such a trend inevitably necessitates a clear guideline (the formulation and application of sustainable trail management approach) not only for establishing trails heritage as safe, quality accredited (audited) and branded products but also for meeting trail development and maintenance international standards and best practices. Through the review of the literatures on trails and trails management for adventure tourism, participation in the Trail Standards Guidelines (TSG) formulation process for the Great Himalaya Trails (GHT) of Nepal and assessment of Nepal’s trail sites as GHT certified trail auditor by the author; this paper argues that sustainable trail management is trail destination specific innovative approach. It should be understood and applied through the interaction of local practices with global knowledge and best practices. There is pressing need of clear guidelines at trail destinations. Such guidelines can be easy reference for shared engagements and benefits of trail communities and enlightening experience of trails users. The discussion concludes with the case study of GHT as an emerging brand for adventure tourism identity of Nepal. GHT strives for sustained and beneficial tourism management system through effective implementation of the TSG by the means of integrated approach.